Законодавча база антирелігійних кампаній другої половини 1940-х – початку 1960-х років у Радянському Союзі : формування, зміст, результати. - Мочкін, Сергій; Mochkin, Sergei (My University, 2015)
У статті охарактеризовано процес складання та зміст нормативно-правових документів, на підставі яких упродовж другої половини 1940-х - початку 1960 рр. у Радянському Союзі, у тому числі й в Українській РСР, здійснювались антирелігійні кампанії. Звернено увагу на результати їх упровадження в життя, підкреслено, що радянське законодавство про релігійні культи відверто підпорядковувалося виконанню завдань антирелігійної політики тодішньої компартійно-державної влади.The article describes the process of creation of normative-legal acts on the basis of which, during the second half of 1940 - in the beginning of the 1960s, carried out anti¬religious campaign in the Soviet Union including Ukraine SSR. The content of the basic laws and regulations of the USSR, the Central Committee of the Communist Party of the Soviet Union party documents, in particular, some of the secret instructions of that period are analyzed. It is mentioned that the Soviet legislation on religious cults openly subordinated to the objectives of the anti-religious policy of the Party and the state power of those times.
The Legal Framework of Anti-religious Campaigns of the Second half of 1940 - the Beginning of the 1960s in the Soviet Union: the Formation, Content and Results
Keywords: антирелігійна кампанія; культова споруда; anti-religious campaign; a legal act; religious building; the law on religious cults; Council for Russian Orthodox Church; the Council for Religious Affairs